2022
DOI: 10.1177/00302228221108293
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Health in Iranian Patients With Cardiovascular Diseases: A Systematic Review and Meta-analysis

Abstract: This systematic review and meta-analysis aimed to evaluate the spiritual health status of Iranian patients with cardiovascular diseases. A literature search was conducted in national (MagIran and Scientific Information Database) and international (Scopus, PubMed, and Web of Science/ISI) databases from inception to December 2021. A random-effects model was used to estimate the pooled score of spiritual health. Based on the eligibility criteria, 22 articles were selected for the final analysis. The pooled score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Rashidzadeh et al showed that spirituality and religious beliefs can improve the well-being and psychological well-being of mothers with autistic children and increase their resilience (23). In addition, the findings of some other previous studies showed that religious coping has a direct relationship with resilience (24)(25)(26). In explaining the results of the present study, one of the ways that spirituality can increase the effectiveness in patients' quality of life is to increase the positive characteristics in life.…”
Section: Discussionsupporting
confidence: 71%
“…Rashidzadeh et al showed that spirituality and religious beliefs can improve the well-being and psychological well-being of mothers with autistic children and increase their resilience (23). In addition, the findings of some other previous studies showed that religious coping has a direct relationship with resilience (24)(25)(26). In explaining the results of the present study, one of the ways that spirituality can increase the effectiveness in patients' quality of life is to increase the positive characteristics in life.…”
Section: Discussionsupporting
confidence: 71%
“…Future studies that use data where the measures do not overlap could investigate whether the results are replicated. Finally, there is a need to consider the non-inclusion of other variables that can have potential influence on this context due to the omission of its measurement in the SHARE protocol, for example, spirituality, which seems to play a key role in the adaptation of patients with cardiovascular risk and could enhance psychological health and reduce psychological disorders [89]. Also, further research could additionally improve the predictive power and the understanding of the process attending other variables.…”
Section: Discussionmentioning
confidence: 99%